Factors Affecting Unemployment Rate: The Case of Afghanistan - Zamani, Sayed Mustafa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
This article aims to analyze the factors that affect the unemployment rate in Afghanistan. The study uses OLS model with time series data from 2005 to 2021 to investigate the effects of macroeconomic factors such as inflation rate, trade balance, GDP, and FDI on unemployment. This article also explores the factors that drive employment in Afghanistan and their potential for decrease. The findings indicate that all factors have a substantial and detrimental influence on unemployment, but that GDP and FDI have more profound impacts and are more crucial for improving employment opportunities in Afghanistan. The result of this study agrees with the theories that suggest that the above-mentioned factors have a huge impact on the rate of unemployment in the case of Afghanistan.